PENERAPAN PENDIDIKAN KARAKTER DI SEKOLAH - Rahmat, Pupu Saeful (Dinamika, 2014)
Abstract. Theoretically the adolescent psychological development is a transition periodwhich is marked by changes in biological, psychological and social aspects. Empirically,the increasing trend of juvenile delinquency is caused by the inability of the earlyadolescents to be assertive so that their personality become weak and they can easily fallinto negative things. This study aimed at determining the extent to which environment andmass media have the influence on assertive behaviour and juvenile delinquency trend inJunior High School in West Java Province. The respondents of this research were 458students of Junior High Schools in West Java. Questionnaire was used to collect the data.Samples were chosen by using stratified random sampling technique. Data analysisemployed Structural Equation Modelling (SEM) with two-stages testing: measurementmodel and structural model, using Analysis of Moment Structure (AMOS). The results ofthis study revealed that all hypothetical statements have significant effects. The findingsshowed that the increasing level of studentsâ assertive behaviour can decrease the tendencyof juvenile delinquency in them.Keywords: assertive behaviour, parenting, mass media, juvenile delinquency trend